Assessment of the corrosion behaviour of alloys 825 and 625 in stagnant seawater-effect of temperature and welding - Chicuba, Pedro Claudio Francisco (Centre for Materials Engineering, 2018)
Alloy 825 has been extensively used as a cladding alloy in the gas and oil industry for process piping up to and including the manifolds, separators, wellheads, risers and valves. The outstanding corrosion resistance of alloy 825 against general and localised corrosion attack is attributed to its high Ni, Cr and Mo content. However, corrosion failures of alloy 825 equipment have been observed in offshore environments. Alloy 825 has good weldability and for applications that require exceptional resistance to corrosion, Inconel filler metal 625 is used as ''overmatching composition''. Nevertheless, there is always a threat of galvanic corrosion when two dissimilar alloys are electrically connected. In this study, the corrosion behaviour of alloy 825, alloy 625 weld and alloy 825 weldment have been investigated. Potentiodynamic polarization curves for the alloys were recorded in synthetic seawater across a range of temperatures (30 to 60°C). Mixed potential theory was applied to determine corrosion potentials, rates of corrosion and predict the galvanic effect of coupling alloy 825 to alloy 625 filler metal via welding. Three standard methods were considered to determine the critical pitting temperature (CPT) for alloy 825. Lastly, long-term immersion tests in seawater were conducted to determine the relationship between the laboratory accelerated tests results and the performance of the alloys under real service conditions. The results from the experimental tests revealed that alloy 825 and alloy 625 weld exhibit outstanding corrosion resistance to uniform corrosion, despite the effect of temperature on the corrosion rate of both alloys. The galvanic effect of coupling alloy 825 to alloy 625 via welding is insignificant. The corrosion morphology of alloy 825 and its weldment is temperature dependent. At temperatures below 45 °C, grain boundary attack was observed in alloy 825 samples, while pitting corrosion was observed at temperatures higher than 50 °C. Alloy 625 weld exhibited only one mode of corrosion attack, namely the selective dissolution of interdendritic phase throughout the test temperature range. There was no agreement between the CPT results for alloy 825 and its weldment obtained using the three standard methods. No correlation was found between CPT determined by laboratory tests and the temperature above which alloy 825 would suffer pitting corrosion in long term seawater exposure tests.